Analysis of failures in open pit mines and consideration of the uncertainty when predicting collapses - Cabrejo-Liévano, A.G. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
The Inverse Velocity (IV) Method, by Fukuzono (1985), has been used in the mining industry along with slope monitoring radars for almost a decade to predict collapses, with significant successes but also with certain limitations due to the uncertainty associated with the method and the characteristics of the different mechanisms of failure in rock masses. This paper summarises the results of research undertaken on 74 pit wall failures, on high and low walls, in different type of mines all over the world, since 2004. Only the characteristics of the failures associated with the application of Fukuzono’s method are discussed. The results are presented statistically, aiming to illustrate the different values of inverse velocity at collapse that could be achieved and the possible errors when forecasting the time of collapse. Keeping in mind the variability of results are essential to a successful risk management at any open pit mine. Some discussions on the type of inverse velocity plots and its possible association to different failure mechanism are also presented for geotechnical practitioners to be aware of when forecasting collapses.